Relationship of Knowledge and Attitude of Nurses With Compliance With Standard Application of Precautions In Hospital - Endah Rusdiana; Eko Suhartono; Lenie Marlinae; Erida Wydiamala (Jurnal Berkala Kesehatan, 2022)
The highest risk of occupational health hazards occurs in health care workers. Several studies explained that nurses' knowledge and attitudes were related to compliance with the application of standard precautions in hospitals. This study aimed to examine studies that explain the relationship between knowledge and attitudes of nurses with compliance with standard application of precautions in hospitals. This study used meta-analysis. Articles that were analyzed used crossectional design. The data sources used Garuda Portal, Google Scholar, PubMed, DOAJ and Science Direct published in last 5 years. Pooled Odds Ratio (pOR) was calculated using fixed-effect and random-effect model. Data were analyzed by Review Manager 5.4. Knowledge variable used 9 studies and attitude variable used 7 studies. The results showed that there was a relationship between nurses' knowledge and compliance with the application of standard precautions in hospitals with p value < 0,0001 and a pooled odds ratio value of 4,69 (95% CI = 2,52 – 8,74). The relationship between nurses' attitudes and adherence to standard precautions in hospitals with p value < 0,03 and pooled odds ratio value of 2.34 (95% CI = 1,11 – 4,91). The conclusion was there was relationship between knowledge and attitudes of nurses with compliance with the application of standard precautions in hospitals.